Proposed Marketing Strategy to Reach 1 Million Members Value for A New Venture in Travel Industry (Case Study: Jar Travels, The Travel Community) (The Indonesian Journal of Business Administration, 2014)
Abstract. In 2013, WTCC (2014) stated that total travel and tourism provided a massive input to the global economy, The numbers not only has displayed a massive contribution of global tourism and travel to the world economy, but it also shown a great potential of this business in the future globally.Indonesia is the country that has strong performance in the region. Stated as one the biggest contributor demand for business travel in the next 10 years. Indonesian travel market growth estimate in 2012 until 2020 about 5.9 % per year. JAR Travels is a start up company, in traveling industry. It positioned the company as travel community, aimed to grab members to join the company in order to utilize the community further. JAR Travels targeted to grab 1 million members in the following four years, but in the first year they only achieved 0.04% from the target. Gap between target and reality becoming issue of this research, and the objective of this research is to propose the solutions to reach the target. In order to formulate the solutions, the situational analyses were conducted to find the root caused. S.T.P and Marketing Mix analysis were done by collecting data of existing condition from the company, completed with 5C analysis to scan the external situation and internal company environments. The result of the analysis were found that the root caused of the problems was un-effective current marketing strategy due to un-clear STP, marketing mix and the marketing communication.From the analysis, JAR Travels is proposed to implement new marketing strategy to achieve membership target. The proposed strategy is using market penetration and proposed the new segmenting and targeting as the new marketing strategy, free membership as the product modification, the system or media to generate and maintain member, and also the replacement of MLM to Internet Referral Marketing.Keyword: strategic marketing, online travel community, referral marketing, word of mouthÂ